Comparison of Low Dose Versus High Dose Statin Therapy in Improving Dyslipidemia - Rehman, Moneeb Ur; Shah , Syed Nadir; Khan, Hasil; Mansoor, Javeria; Fazal ur Rehman; Manzoor, Rida; Kakar, Sana Ullah (Indus Journal of Bioscience Research, 2024)
Dyslipidemia, a significant contributor to atherosclerosis and its associated conditions like coronary artery disease, cerebrovascular disease, and peripheral vascular disease, requires effective management through lifestyle changes and pharmacological treatment. Statins are commonly used to reduce low-density lipoprotein (LDL) cholesterol levels, thus lowering the risks of myocardial infarctions and strokes. However, higher doses of statins, while more effective in reducing cardiovascular events, are associated with an increased risk of adverse effects such as myopathy and elevated liver enzymes. This study aimed to compare the efficacy of low-dose (10 mg) versus high-dose (40 mg) atorvastatin therapy in improving lipid profiles in patients with acute coronary syndrome (ACS).A randomized trial was conducted with 90 ACS patients recruited from the Bolan Medical Complex, Quetta. They were randomly assigned to either receive 10 mg or 40 mg atorvastatin daily for four months. Lipid profiles, including HDL-C, LDL-C, triglycerides, and total cholesterol, were measured before and after the intervention. Both dosage groups showed significant improvements in their lipid profiles after the treatment period. However, there was no statistically significant difference between the two groups in the overall improvement of dyslipidemia. These findings suggest that both low and high doses of atorvastatin are effective in improving lipid profiles, but higher doses may not offer additional benefits in this patient population.